Coregonus pidschian ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Coregonus pidschian (Gmelin, 1789). Humpback Whitefish. To 54 cm (31.5 in) TL. Along Arctic coasts from Siberia, Russia, west to Kara Sea, and eastward along Alaska and Canadian coasts to Hudson Bay and New England (as Clupea clupeaformis of Canadian authors). American biologists have generally referred to anadromous and Alaska-dwelling individuals of this species as “humpback” whitefish, Coregonus pidschian. Anadromous fish in northern Canada usually have been called “lake” whitefish (Coregonus clupeaformis (Mitchill, 1818)) by Canadian researchers. Following McDermid et al. (2007), we refer to the individuals residing from the Alaska Peninsula to the U.S. Chukchi and Beaufort Sea drainages and eastward at least to the lower Mackenzie River as this species. All in Love et al. (2016). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 53, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...